An Afrocentric exploration of South Africa's homeland policy with specific reference to VhaVenda Traditional Leadership and Institutions, 1898-1994 - Mahosi, Theodore Nkadimeng (My University, 2020)
The subject of traditional leadership has been, and will always be, the subject of academic debate in various disciplines and varying objectives throughout the years. However, it is in South Africa to a large extent, but Venḓa specifically, that this study focuses on the discussion on the controversial subject of vhuhosi (traditional leadership) within the homeland system. This study specifically identifies vhuhosi and institutions of Vhavenḓa as a topic for research given its muddied history during the dark days of colonial subjugation and apartheid oppression and suppression. It is for this reason that this study explores South Africa’s homeland policy with specific reference to vhuhosi of Vhavenḓa and institutions (1898-1994). In order to do this the study starts by describing the nature of the relationship between the South African government and vhuhosi of Vhavenḓa on the eve of homeland policy as a way of setting the tone of the Afrocentric exploratory paradigm. The objective is to expose the gradual political and socio-economic changes that vhuhosi and institutions of Vhavenḓa were subjected to during South Africa’s political development. The study then analyses the development of ethnicity vis-à-vis the influence of ethnic identity during the period surrounding the establishment of Vhavenḓa homeland. Given this background it then describes the changing power relations between the South African government and mahosi within the Venḓa homeland. Significantly, the study examines the impact of Vhavenḓa homeland on the internal relations among mahosi of Vhavenḓa as well as Vhavenḓa’s cultural conception of royalty and governance. The current researcher identifies the Afrocentric theory as a vehicle to embark on the explorative nature of this study. Unlike other theoretical paradigms that conducted research on vhuhosi and institutions for colonial and apartheid objectives, the Afrocentric approach was preferred as it puts African values at the centre. Therefore the Afrocentric theory was preferred as a way of debunking the Eurocentric/Western and liberal research on African subjects such as vhuhosi and institutions. Hence oral interviews played an important role to complement the written and archival material available.
Thesis (Ph.D. (History)) -- University of Limpopo, 2020
Keywords: Vhuhosi and institutions; African values; Vhavenḓa, homeland; Apartheid; Ritual murder; Witch-hunting; Witch-burning; Chiefdoms -- South Africa -- Limpopo; Afrocentrism; Democracy -- South Africa -- Limpopo; Homelands (South Africa); Venda (African people)